PENERAPAN MODEL LEARNING CYCLE 5E UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK - Jayantri, Ysiyar (STKIP PGRI Bandar Lampung, 2019)
The problem of this research is motivated by the lack of optimal thematic learning outcomes of class IV D students of Negeri 1 Sukarame Elementary School. The purpose of this study was to analyze, describe, and know the improvement of student learning outcomes through the application of the 5E learning cycle model. The research method used is classroom action research (PTK) which is carried out in 2 cycles, each cycle consisting of the stages of planning, implementation, observation, and reflection. The technique of collecting data is done by observation and test questions. The analysis technique used is qualitative and quantitative analysis. The results of the study show that through the application of the 5E learning cycle model can improve the thematic learning outcomes of students. This can be seen from the percentage of classical completeness in student learning outcomes in the first cycle is (61.5%) with the category